KONSERVASI SUMBER DAYA TAMAN HUTAN RAYA NGURAH RAI SEBAGAI DESTINASI EKOWISATA - Manurung, Vina Trisha; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i02.p04, 2016)
This study discusses the conservation of Ngurah Rai Forest Park as a nature resources to make it as ecotourism destination. This park has been launched as an area of ??Ngurah Rai Mangrove Forest Park, so this area has the potential to serve as an ecotourism destination. This study aims to determine the tourism potential that Ngurah Rai Forest Park has and conservation efforts of the government as regulator to keep and maintain the existing of Ngurah Rai Forest Park as one of the ecotourism destination. Data obtained from one of the office in Denpasar that administer the park which is the Unit Pelaksana Teknis (UPT) Ngurah Rai Forest Park,, with data collection techniques which are observation, interviews, and literature study. Determination of informant was done by using purposive sampling technique. The data analysis technique used is descriptive qualitative. It can be concluded about Ngurah Rai Forest Park physical potential (natural) which are mangrove forest panorama, approximately 1.400m tracking path, and the existing as a conservation area for mangrove forests and various animals. Ngurah Rai Tahura conservation efforts have been implemented since 1991-present, government in cooperation with the Japan International Cooperation Agency (JICA) make a wide variety of projects such as Mangrove Information Center (MIC) Project that include a construction of a Mangrove Museum that provide informations about the mangrove ecosystem in Indonesia and also in the whole world.
Keywords: conservation, forest park , Ngurah Rai , ecotourism